Apical-to-basolateral transcytosis of photoreceptor outer segments induced by lipid peroxidation products in human retinal pigment epithelial cells - Krohne, Tim Ulrich; Holz, Frank G.; Kopitz, Jürgen (Investigative ophthalmology & visual science, 2010)
Progressive accumulation of extracellular material at the basolateral side of the retinal pigment epithelium (RPE) is a key event in the pathogenesis of age-related macular degeneration (AMD). The authors previously demonstrated that modifications with lipid peroxidation products, such as 4-hydroxynonenal (HNE) and malondialdehyde (MDA), stabilize photoreceptor outer segment (POS) proteins against lysosomal degradation. Herein, they tested RPE cells for the basolateral release of undegraded modified POS proteins. Polarized cultures of the human RPE cell line ARPE-19 on permeable membranes were incubated with iodine-125-labeled POS on the apical side. After 24 hours, radioactivity was quantified in apical medium, cell lysates, and basolateral medium after separation of undegraded proteins by precipitation. Protein composition of basolaterally released POS material was analyzed by two-dimensional gel electrophoresis. C3a- and SC5b-9-specific enzyme-linked immunosorbent assays were used to assess complement activation by modified POS. The amount of phagocytic uptake was similar for native and modified POS. Unmodified POS proteins were almost completely (98.1%) degraded, whereas degradation of HNE- and MDA-modified POS proteins was significantly reduced (47.2%; 56.5%). Undegraded POS proteins accumulated intracellularly (14.2%; 12.1%) and were trafficked through the cells to be released into the basolateral medium (38.5%; 31.5%). Protein composition of basolaterally released material matched the original POS preparations. Protein modifications did not confer increased complement-activating capacity to POS material. Inhibition of lysosomal degradation by lipid peroxidation-related protein modifications induces apical-to-basolateral transcytosis of undegraded POS proteins by human RPE cells in vitro. This mechanism may contribute to sub-RPE deposit formation and drusen biogenesis in AMD.
Gesehen am 06.03.2023